Effects of the tax liability of managers on the relationship between tax infraction notices and tax avoidance - Fabiano de Castro Liberato Costa; Roberto Carlos Klann (Revista Contabilidade & Finanças, 2024)
ABSTRACT The aim of this research was to assess the moderating role of the joint and several liability of company directors in the relationship between the cumulative value of tax infraction notices and the subsequent level of corporate tax avoidance. Based on agency theory, the literature suggests that penalizing managers is more effective in reducing tax avoidance than penalizing the firm itself. However, this proposition had not been tested in Brazil, where the legislation determines that infraction notices and the consequent penalization of companies are carried out with the joint and several liability of the directors who have acted in excess of their powers or in violation of the law, the articles of incorporation, or the bylaws. The research is relevant because it presents empirical findings on the determinants of tax avoidance in large companies, as well as demonstrating the importance of the establishment of tax liability in controlling tax avoidance. This research has implications for the public debate on the establishment of tax liability, particularly its role in deterring tax avoidance. As a practical implication, it is suggested that the tax authority prioritizes tax audits that provide evidence that could lead to the tax liability of directors. The research consisted of a multiple linear regression analysis using the ordinary least squares (OLS) method on 23,142 observations from 4,560 large companies, covering the period from 2014 to 2020, collected directly from the internal systems of the Brazilian Federal Revenue Office (RFB). The results suggest that the joint and several liability of directors attenuates (intensifies) the positive relationship between the cumulative value of tax infraction notices and tax avoidance, as measured by the book tax difference (BTD) [effective tax rate (ETR)], contributing to the literature by confirming, in relation to current taxes, the theoretical prediction that penalties applied to directors are more effective, from the point of view of the tax authority, in controlling tax avoidance.